Cancer during pregnancy: from the diagnosis to the repercussions on the family experience of maternity - Joseila Sonego Gomes; Isabel Cristina Pacheco Van der Sand; Nara Marilene Oliveira Girardon-Perlini (SciELO, 2021)
ABSTRACT Objective: To investigate how the diagnosis of cancer during pregnancy occurred and assess its repercussions on the family experience of maternity. Method: Qualitative research, based on Symbolic Interactionism and conducted according to the Grounded Theory method. Twelve women diagnosed with cancer during pregnancy and 19 of their family members participated in the study. Data was collected from March 2018 to March 2019, using an identification form and an in-depth interview. The analysis followed the stages of open substantive coding. Results: Data were organized into two categories of analysis: Being surprised by the discovery of cancer during pregnancy, which reveals the course of experiencing pregnancy and being diagnosed with cancer, Suffering from the repercussions of cancer on pregnancy and birth, which describes the repercussions of illness in the experience of pregnancy. Conclusion: Cancer during pregnancy was diagnosed in young women based on signs and symptoms that were confused with those of pregnancy and postpartum. The illness brought anxiety, impotence, fear and affected the experience of maternity, as it prevented women from having their pregnancy as planned and required routines different from those of low-risk pregnancies.